2021
DOI: 10.1515/ncrs-2020-0526
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of methacholine chloride, C8H18ClNO2

Abstract: C8H18ClNO2, monoclinic, P21/c (no. 14), a = 6.8110(5) Å, b = 8.8779(7) Å, c = 17.2774(16) Å, β = 97.582(4)°, V = 1035.59(15) Å3, Z = 4, R gt (F) = 0.0484, wR ref (F 2) = 0.0922, T = 200 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…A survey of the Cambridge Structural Database (version 5.45, November, 2023;Groom et al, 2016). yields only two known prior examples of structures containing 2CLEA + : an (Mo 2 O 2 Cl 8 ) 2À salt (CSD refcode POSWAX; Marchetti et al, 2015), in which the gauche conformation is found, and a chloride salt (CSD refcode: URORUR; Muller et al, 2021) where the anti conformation is found, albeit with a disordered alkyl chain. For 3CLPA + , besides the aforementioned chloride salt there is one other structure containing 3-chloro-N,N-propan-1-amine as a ligand in a di(�-hydrido) dialuminium complex (CSD refcode: NIGGOZ; Andrews et al, 1997) where the gauche conformation is also found.…”
Section: Database Surveymentioning
confidence: 99%
“…A survey of the Cambridge Structural Database (version 5.45, November, 2023;Groom et al, 2016). yields only two known prior examples of structures containing 2CLEA + : an (Mo 2 O 2 Cl 8 ) 2À salt (CSD refcode POSWAX; Marchetti et al, 2015), in which the gauche conformation is found, and a chloride salt (CSD refcode: URORUR; Muller et al, 2021) where the anti conformation is found, albeit with a disordered alkyl chain. For 3CLPA + , besides the aforementioned chloride salt there is one other structure containing 3-chloro-N,N-propan-1-amine as a ligand in a di(�-hydrido) dialuminium complex (CSD refcode: NIGGOZ; Andrews et al, 1997) where the gauche conformation is also found.…”
Section: Database Surveymentioning
confidence: 99%